Gait characteristics of elderly people with a history of falls: a dynamic approach. - Barak Y; Wagenaar RC; Holt KG (Physical Therapy, 2006)
BACKGROUND AND PURPOSE: This study investigated changes in the kinematics of elderly people who experienced at least one fall 6 months prior to data collection. The authors hypothesized that, in order to decrease variability of walking, people with a history of falls would show different kinematic adaptations of their walking patterns compared with elderly people with no history of falls. SUBJECTS AND METHODS: Twenty-one elderly people who had fallen within the previous 6 months ('fallers'; mean age=72.1 years, SD=4.9) and 27 elderly people with no history of falls ('nonfallers'; mean age=73.8 years, SD=6.4) walked at their preferred stride frequency (STF) as treadmill speed was gradually increased (from 0.18 m/s to 1.52 m/s) and then decreased in steps of 0.2 m/s. Gait parameter measurements were recorded, and statistical analysis was applied using walking speed and STF as independent variables. RESULTS: Fifty-seven percent of the fallers were unable to walk at the fastest speed, whereas all nonfallers walked comfortably at all walking speeds. Although the fallers showed significantly greater STF, smaller stride lengths, smaller center-of-mass lateral sway, and smaller ankle plantar flexion and hip extension during push-off, they showed increased variability of kinematic measures in their coordination of walking compared with the nonfallers. DISCUSSION AND CONCLUSION: Although the fallers' adaptations were expected to reduce variability in the coordination of walking, they showed less stable gait patterns (ie, greater variability) compared with the nonfallers. Increased variability of walking patterns may be an important gait risk factor in elderly people with a history of falls.